Not So! Popular Myths About America From Columbus to Clinton - Paul F Boller (U.S.A Oxford University Press, 1995)
In sailing westward in 1492, did Columbus defy the prevailing belief that the Earth was flat? Was Thomas Paine an atheist? Was Truman plucked from obscurity to be F.D.R's running mate in 1944? Are presidential campaigns nowadays far dirtier than they were in the past? Is Hillary Clinton the most active or influential First Lady ever? Not so, says Paul Boller, in this delightfully informative look at some of the most common myths and misconceptions about the American past. As he did in his bestselling They Never Said It, Boller provides us with a cornucopia of historical correction, debunking myths that range from the trivial-for instance, George Washington did not have false teeth made of wood (they were made of ivory)-to the pernicious (F.D.R. did not know in advance that the Japanese planned to bomb Pearl Harbor). We learn that most educated people in Columbus's day knew the world was round (it was Washington Irving who first portrayed Columbus as defying a coterie of flat-earthers); that Washington's famous Farewell Address was mostly written by Alexander Hamilton; that the Pledge of Allegiance was penned by Francis Bellamy, a devout socialist, in 1892 (and it was intended as a paean to big government); that Thomas Paine was not an atheist, but a deist (as were Washington, Jefferson, and Franklin), and his Age of Reason attacked both organized religion and atheism; that Truman was far from an obscure politician in 1944 (he had been on the cover of Time in 1943 for his Senate work uncovering waste and fraud in the war industries, and a Look magazine poll placed Truman among the ten figures who had contributed the most to the war effort); that presidential campaigns in the old days were more vituperative than recent ones; and that several First Ladies were more influential than Hillary Clinton, most notably Eleanor Roosevelt and Edith Wilson (the latter played a crucial role in her husband's administration from 1919
Keywords: History of Countries -- History of Countries; History of The Americas -- History of The Americas